What are effective strategies to respond to the psychological impacts of working on the frontlines of a public health emergency? - Sarah E. Neil-Sztramko; Sarah E. Neil-Sztramko; Emily Belita; Stephanie Hopkins; Diana Sherifali; Laura Anderson; Emma Apatu; Lydia Kapiriri; Jean Eric Tarride; Jean Eric Tarride; Jean Eric Tarride; Olivier Bellefleur; et al. (Frontiers Media S.A., 2023)
BackgroundThe COVID-19 pandemic has disrupted the healthcare and public health sectors. The impact of working on the frontlines as a healthcare or public health professional has been well documented. Healthcare organizations must support the psychological and mental health of those responding to future public health emergencies.ObjectiveThis systematic review aims to identify effective interventions to support healthcare workers' mental health and wellbeing during and following a public health emergency.MethodsEight scientific databases were searched from inception to 1 November 2022. Studies that described strategies to address the psychological impacts experienced by those responding to a public health emergency (i.e., a pandemic, epidemic, natural disaster, or mass casualty event) were eligible for inclusion. No limitations were placed based on study design, language, publication status, or publication date. Two reviewers independently screened studies, extracted data, and assessed methodological quality using the Joanna Briggs Institute critical appraisal tools. Discrepancies were resolved through discussion and a third reviewer when needed. Results were synthesized narratively due to the heterogeneity of populations and interventions. Outcomes were displayed graphically using harvest plots.ResultsA total of 20,018 records were screened, with 36 unique studies included in the review, 15 randomized controlled trials, and 21 quasi-experimental studies. Results indicate that psychotherapy, psychoeducation, and mind-body interventions may reduce symptoms of anxiety, burnout, depression, and Post Traumatic Stress Disorder, with the lowest risk of bias found among psychotherapy interventions. Psychoeducation appears most promising to increase resilience, with mind-body interventions having the most substantial evidence for increases in quality of life. Few organizational interventions were identified, with highly heterogeneous components.ConclusionPromoting healthcare workers' mental health is essential at an individual and health system level. This review identifies several promising practices that could be used to support healthcare workers at risk of adverse mental health outcomes as they respond to future public health emergencies.Systematic review registration: https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=203810, identifier #CRD42020203810 (PROSPERO).